Optimization of Cardamom Fruit (Amomum compactum) Extraction Focused on Total Terpenoid Extraction and Cytotoxic Activity Using Response Surface Methodology - Juliana, Dara; Priosoeryanto, Bambang Pontjo; Nurcholis, Waras (Jurnal Jamu Indonesia, 2023)
Cardamom is one of the medicinal plants called perennial herbs from the Zingiberaceae family. Cardamom, with the scientific name Amomum compactum, contains various phytochemical compounds such as terpenoids, flavonoids, phenolics, tannins, sterols, and proteins that are pharmacologically useful as an anticancer, antioxidant, and have cytotoxic activity. Testing the total content of terpenoid compounds that affect the cytotoxic activity of A. compactum fruit using Box-Behnken Design with three independent variables (solvent ratio, ethanol concentration, and extraction time) has never been studied before. Thus, this study aimed to obtain the extraction optimization conditions on the total terpenoid content and cytotoxic activity using Artemia salina Leach larvae with the response surface method, namely Box-Behnken Design with Design Expert 13.0 application. Determination of the total terpenoid content of the A. compactum fruit extract was carried out based on the standard ursalic acid, and the cytotoxic activity was carried out using the Brine Shrimp Lethality Test (BSLT) method. The maximum total terpenoid obtained was 4.8970 mg UAE/g DW, and the minimum IC50 value was 38.8813 ppm. Optimal conditions for the extraction of A. compactum fruit obtained a combination of 1:8 mL/g solvent ratio, 50% ethanol concentration, and extraction time of 1 day with a desirability value of 0.772. Furthermore, the optimal extraction solution results from the Box-Behnken Design were verified and analyzed using a One-Sample T-Test. Using the Box-Behnken Design extraction optimization method, the content of terpenoid bioactive compounds with cytotoxic activity from A. compactum fruit can be optimally obtained.